Spawning lake sturgeon (Acipenser fulvescens Rafinesque, 1817) and their habitat characteristics in Rainy River, Ontario and Minnesota. (24th April 2017) - Smith, A.; Smokorowski, K. E.; Power, M.
Summary: Lake Sturgeon ( Acipenser fulvescens ) spawning habitat in the Rainy River was studied in light of the ongoing review of the rules governing water levels upstream that affect discharge rates through the International Falls dam. The objectives of this study were to assess the current status of spawning Lake Sturgeon below the dam by: (i) evaluating weight–length relationships, condition, age and growth; (ii) identifying spawning locations and characterizing its physical attributes; and, (iii) evaluating the effects of water surface elevation on the availability of spawning habitat. Spawning was confirmed with use of egg mats, and targeted sampling of spawning individuals was completed using gillnets and electrofishing. Physical attributes of spawning locations, including temperature, depth and water velocity were collected at a range of water levels using an Acoustic Doppler Current Profiler and representative sediment sampling. Biological characteristics and timing of spawning events were consistent with those previously reported for Lake Sturgeon. However, a wider range of depths (0.3–10.5 m) and velocities (0.01–1.9 m 3 /s) than reported in most single site studies was found here, with the ranges encompassing what is reported in the literature as a whole. Lake Sturgeon were found to prefer coarse spawning substrates dominated by bedrock, boulder or cobble. The availability of preferred spawning habitat varied significantly with the changing water levels observed during the study and was eventually limited at higher water levels by river channel form. Because of the implications for dewatering of nest sites, keeping flows constant during spawning is critical to Rainy River Lake Sturgeon spawning success.